Occurrence of Eriochloa distachya and Parodiophyllochloa penicillata (Poaceae) in São Paulo State, Brazil - Rodrigues, Rodrigo Sampaio; Filgueiras, Tarciso Sousa (Phytotaxa, 2013)
Two species of Poaceae (Eriochloa distachya and Parodiophyllochloa penicillata) are newly reported for the state of São Paulo, Brazil. This paper includes descriptions, illustrations, and comments on the distribution and conservation statuses of these taxa in São Paulo.